Exploring Wholly Doped Conjugated Polymer Films Based on Hybrid Doping: Strategic Approach for Optimizing Electrical Conductivity and Related Thermoelectric Properties - Yoon, Sang Eun; Kang, Yeongkwon; Jeon, Gyeong G.; Jeon, Dohyeon; Lee, Sang Yeon; Ko, Seo Jin; Kim, Taekyeong; Seo, Hyungtak; Kim, Bong Gi; Kim, Jong H. (Advanced Functional Materials, 2020)
Conventional chemical doping processes for conjugated polymers (CPs) often degrade the film morphology or cause unsatisfactory doping efficiency owing to the aggregation formation between charged species or insufficient dopant diffusion. In this work, a new strategic doping method, “hybrid doping,” is suggested for maximizing the doping efficiency of CPs without hampering the surface morphology of the CP films. The advantage of hybrid doping is that it combines mixture blending and sequential soaking processes. Based on systemic characterizations including spectroscopic, structural, and electrical analyses, it is revealed that hybrid doping enables whole area doping for the crystalline and amorphous regions of CP films, and thus an unprecedentedly high electrical conductivity of up to 81.5 and 639.1 S cm−1, for poly(3-hexylthiophene) P3HT and poly (2-([2,2′-bithiophen]-5-yl)-3,8-difluoro-5,10-bis(5-octylpentadecyl)-5,10-dihydroindolo [3,2-b]indole) (PIDF-BT), respectively, is achieved. Furthermore, the exceptional electrical conductivity compensates a reduced Seebeck coefficient, resulting in excellent power factors up to 26.8 and 76.1 μW m−1 K−2 for thermoelectric devices based on doped-P3HT and PIDF-BT films, respectively, which is among the highest levels for semiconducting CPs. Hybrid doping is a strategic approach for the simultaneous optimization of electrical conductivity and thermoelectric properties of various CPs.
Keywords: Electrical analysis; Electrical conductivity; High electrical conductivity; Poly (3-hexylthiophene); Simultaneous optimization; Strategic approaches; Thermoelectric devices; Thermoelectric properties; conjugated polymers; electrical conductivity; hybrid doping; molecular doping; thermoelectric effect